(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In this study, dental, heart and lung diseases in patients with Covid-11 and hospitalized in ICU have been investigated based on radiology stereotypes. During the past months, it has been determined that the risk of this disease is greater for some people who have heart and lung diseases or suffer from complications such as high blood pressure and diabetes, and it is necessary for this group of people to be more careful. lack of contact with sick people, so that many of these people, who were under regular medical care before the corona disease, refuse to see a doctor due to the fear of being in environments infected with the corona virus, such as offices and clinics and naturally, the amount of previous care and sensitivities has been reduced, an issue that can be seen even in people without primary disease and with the onset of the first disease. During the past months, it has been abundantly observed that people with symptoms of heart attacks and heart failure have refused to go to the medical center and emergency system due to the fear of medical centers, and unfortunately, this issue causes delays in treatment and sometimes even irreversible complications. It has been compensated. People who have a history of heart disease and regularly use drugs should communicate with their doctor about the effectiveness of the drugs, their side effects and the need to change the drugs on a regular basis. Not going to the doctor does not mean disconnection from the treatment system and this can lead to many complications. People with heart disease or high blood pressure happen to be more at risk of complications from corona disease than other people, and if they are infected, their symptoms are more severe and the possibility of complications of the disease is more in them than others. Therefore, it is necessary for these people to use medical advice as soon as symptoms related to the disease appear. Denial of the disease and fear of going to the medical center can delay the diagnosis and the subsequent complications of the disease.